Misuse Detection System Using Various Techniques: A Review (International Journal of Advanced Research in Computer Science, 2017)
In the era of information systems and internet there is more concern rising towards information security in day to day life, along withthe availability of the vulnerability assessment mechanisms to identifying the electronic attacks. Traditionally intrusion detection systems (IDS)are classified based on the style of detection they are Using. Ther are two main categories of intrusion detection (ID) those are misuse detectionand anomaly detection.This paper mainly concerned about misuse detection system (MDS). In misuse detection, the IDS analyzes theinformation it gathers and compares it to large databases of attack signatures. Essentially, the IDS looks for a specific attack that has alreadybeen documented. Like a virus detection system, misuse detection software is only as good as the database of attack signatures that it uses tocompare packets against.Keywords: Intrusion detection system (IDS),Misuse detection system(MDS),pattern matching, Artificial neural network, data mining with fuzzylogic and genetic algorithms.